2007
DOI: 10.1145/1187436.1216584
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms for pure Nash equilibria in weighted congestion games

Abstract: In large-scale or evolving networks, such as the Internet, there is no authority possible to enforce a centralized traffic management. In such situations, game theory, and especially the concepts of Nash equilibria and congestion games [Rosenthal 1973] are a suitable framework for analyzing the equilibrium effects of selfish routes selection to network delays. We focus here on single-commodity networks where selfish users select paths to route their loads (represented by arbitrary integer weights). We assume t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 12 publications
3
34
0
Order By: Relevance
“…Also related is the early work of Rosenthal [33] who showed that in weighted congestion games where players are allowed to split their demand integrally, a PNE need not exist. On the positive side, Fotakis et al [16] and Panagopoulou and Spirakis [30] proved the existence of a PNE in games with affine and exponential costs, respectively. Dunkel and Schulz [13] showed that it is strongly NP-hard to decide whether or not a weighted congestion game with nonlinear cost functions possesses a PNE.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Also related is the early work of Rosenthal [33] who showed that in weighted congestion games where players are allowed to split their demand integrally, a PNE need not exist. On the positive side, Fotakis et al [16] and Panagopoulou and Spirakis [30] proved the existence of a PNE in games with affine and exponential costs, respectively. Dunkel and Schulz [13] showed that it is strongly NP-hard to decide whether or not a weighted congestion game with nonlinear cost functions possesses a PNE.…”
Section: Related Workmentioning
confidence: 99%
“…(iii) ⇒ (ii) follows because every weighted congestion games with such cost functions possesses a weighted potential; see Fotakis et al [16], Harks et al [22], and Panagopoulou and Spirakis [30].…”
mentioning
confidence: 94%
See 3 more Smart Citations